The bug and the bomb: medical readiness as a national strategic priority. (27th May 2009) - Hopmeier, Michael; Lee, Catherine Y.; Lowell, Jeffrey A.
Throughout the 20th and 21st centuries numerous threats have developed, matured and grown into what would be considered 'strategic' in nature. Few, however, have had as much impact on our government and its efforts at preparedness as the scourges of terrorism, nuclear war and conventional conflict. In addition, the economic costs for preparation and response to these threats have been great. Among other things, we have developed highly institutionalised and formalised processes for ensuring that these threats are identified, assessed, analysed and reanalysed within a highly complex, robust and multiredundant system to ensure that no single factor is missed and no possibility for preparation is overlooked. There remains a preeminent threat to this nation, one that during this same period of time has cost the USA almost 4.5 times as many lives (3.2 million) and nearly 7 times the expense ($4.7 trillion) as the terror, nuclear and conventional threats combined. This threat is infectious disease. This article discusses infectious diseases in comparison with other strategic threats facing our nation. This article discuss the process of creating a strategic plan which is both vital and well within our understanding and existing current processes to develop, similar to concepts applied in preparation for more conventional threats.